IMPLEMENTASI KEBIJAKAN SISTEM INTEGRASI TRANSPORTASI PUBLIK JAK LINGKO PADA LAYANAN ARMADA MIKROTRANS WILAYAH TRAYEK JAKARTA TIMUR - Dafa Riansyah; Satria Aji Imawan (Journal of Management and Public Policy, 2026)
Limited access to public transportation in residential areas remains a major challenge in Jakarta’s urban mobility system. High dependence on private vehicles and non-integrated neighborhood transport services has encouraged the Provincial Government of DKI Jakarta to develop the Jak Lingko public transport integration policy. This policy aims to expand the coverage of public transportation by integrating neighborhood-based transport into a standardized service system, implemented through the operation of Mikrotrans as a feeder service connecting residential areas to main public transport modes. This study aims to analyze the implementation of the Jak Lingko public transport integration policy in Mikrotrans services in East Jakarta and to identify the factors influencing its implementation. This research employs a descriptive qualitative approach. Data were collected through in-depth interviews with representatives of PT Jak Lingko Indonesia, the DKI Jakarta Provincial Transportation Agency, route coordinators, Mikrotrans drivers, and service users. Supporting data were obtained from laws and regulations, institutional reports, scientific literature, and online media coverage. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of the Jak Lingko policy in Mikrotrans services has contributed to expanding public transport coverage and improving intermodal connectivity in East Jakarta. Policy objectives and service standards have been implemented through route arrangements, operational schedules, and non-cash payment systems. However, implementation at the operational level continues to face several challenges, including route overlaps, uncertainty in service schedules due to traffic conditions, limited access to the payment system, and social dynamics on certain routes. The contract-based wage system provides income stability for drivers, although it has not fully reflected adequate welfare levels. These findings suggest that the success of policy implementation is highly dependent on the alignment between policy design and field realities, as well as the quality of coordination among implementing actors.